Estrutura e organização da avifauna do Pantanal, uma savana neotropical inundável : vieses amostrais e lacunas de informação, associações interespecíficas de aves e sua resposta aos efeitos da sazonalidade e da estrutura da paisagem - Fernández Arellano, Gilberto Josimar (2022)
In the last decades, the number of studies on the avifauna of the Pantanal has grown (e.g., spatial and temporal variation). Pantanal birds occur in different types of habitat, from grasslands to forests, participating in associations of the same or several species (e.g., mixed-species flocks). In this study, we evaluated the state of knowledge (biases and knowledge gaps) of the Pantanal birds, but we also evaluated the structure, organization and space use of mixed-species flocks, as a community subset, in relation to seasonality and landscape structure. Our results suggest that most bird studies were carried out close to urban centers and during the dry season. Studies on species behavior were the most frequent, while the families most (e.g., Jacanidae) and least (e.g., Tyrannidae) studied were, respectively, those with fewer and more species. On the other hand, flocks had fewer species, individuals and diversity during the wet season, whereas flocks had more species, individuals and diversity during the dry and flood seasons. There were no differences between dry and flood. Moreover, flocks had more species and individuals at local scale dominated by grasslands, whereas flocks had fewer species and individuals at landscape scale dominated by forest. The proportion of mixed vegetation did not influence the space use of flocks, but the home range varied in response to seasonality. Flocks use less space during the wet season, whereas flocks use more space during the dry and flood seasons. There were no difference between dry and flood.